Tracheal reconstruction using chondrocytes seeded on a poly(l‐lactic‐co‐glycolic acid)–fibrin/hyaluronan. Issue 11 (29th January 2014) - Hong, Hyun Jun; Chang, Jae Won; Park, Ju‐Kyeong; Choi, Jae Won; Kim, Yoo Suk; Shin, Yoo Seob; Kim, Chul‐Ho; Choi, Eun Chang
Abstract Reconstruction of trachea is still a clinical dilemma. Tissue engineering is a recent and promising concept to resolve this problem. This study evaluated the feasibility of allogeneic chondrocytes cultured with fibrin/hyaluronic acid (HA) hydrogel and degradable porous poly(l‐lactic‐co‐glycolic acid) (PLGA) scaffold for partial tracheal reconstruction. Chondrocytes from rabbit articular cartilage were expanded and cultured with fibrin/HA hydrogel and injected into a 5 × 10 mm‐sized, curved patch‐shape PLGA scaffold. After 4 weeks in vitro culture, the scaffold was implanted on a tracheal defect in eight rabbits. Six and 10 weeks postoperatively, the implanted sites were evaluated by bronchoscope and radiologic and histologic analyses. Ciliary beat frequency (CBF) of regenerated epithelium was also evaluated. None of the eight rabbits showed any sign of respiratory distress. Bronchoscopic examination did not reveal stenosis of the reconstructed trachea and the defects were completely recovered with respiratory epithelium. Computed tomography scan showed good luminal contour of trachea. Histologic data showed that the implanted chondrocytes successfully formed neocartilage with minimal granulation tissue. CBF of regenerated epithelium was similar to that of normal epithelium. Partial tracheal defect was successfully reconstructed anatomically and functionally using allogeneic chondrocytes cultured with PLGA‐fibrin/HA composite scaffold. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4142–4150, 2014.